(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2019)
The New York Film Festival Downtown (1984-1989) was, in the strict sense, not a film festival. But then again, it depends on how film is defined. On three nights, on the stage of a downtown night club, films were shown unfinished, as excerpts or slides, they alternated or shared a stage with performance, theater and dance pieces involving projections, or experimental live happenings. This essay articulates that the festival’s messiness–that ‘it wasn’t pristine’, as festival organizer Ela Troyano described it–should above all be considered as its most productive structural element: The New York Festival Downtown both reflected and encouraged the downtown scene’s mixing of media, and its collaborative, experimental, and interdisciplinary practices. In doing so, it not only pushed the format of the film festival, but challenged the notion of film itself. And while remaining a local artist-curated initiative, the festival’s program also traveled, thereby bringing downtown to Berlin, Bielefeld and Buffalo, and stretching the scene’s local boundaries.